The Contribution of Tourist Visits, Hotel and Restaurant Taxes, and the Human Development Index to Local Revenue on Lombok Island - Yunia Ulfa Variana (Lembaga Bale Literasi, 2026)
This study examines the contribution of hotel and restaurant taxes, tourist visits, and the Human Development Index to local government revenue in the regencies and cities of Lombok Island. This study is important for elucidating the relationship between tourism activities, local fiscal capacity, and the quality of human development in regions with a strong tourism base. The data used consists of panel data from five districts/cities on Lombok Island for the period 2017-2024. The analysis was conducted using a fixed-effects model to account for differences in regional characteristics. The results indicate that tourist visits have a positive and significant effect on local government revenue, while the Human Development Index (HDI) also has a positive and significant effect on local government revenue. Conversely, hotel and restaurant taxes have a positive relationship but are not statistically significant. This article discusses that the increase in local revenue on Lombok Island is more strongly explained by the intensity of tourist visits and the quality of human development, while the contribution of hotel and restaurant taxes remains vulnerable to external shocks, collection effectiveness, and variations in local revenue structures across regions.